Coffea canephora Peptides in Combinatorial Treatment with Fluconazole: Antimicrobial Activity against Phytopathogenic Fungus - Gabriela C. V. Bard; Gabriel B. Taveira; Thaynã A. M. Souza; Érica O. Mello; Sávio B. Souza; Alessandro C. Ramos; André O. Carvalho; Lídia S. Pereira; Umberto Zottich; Rosana Rodrigues; Valdirene M. Gomes (International Journal of Microbiology)
The objective of the present study was to evaluate the antimicrobial activity of the Cc-LTP2 and Cc-GRP peptides isolated from Coffea canephora seeds and their possible synergistic activity with the azole drug fluconazole and characterize their mechanisms of action on cells of pathogenic fungi. Cc-LTP2 and Cc-GRP alone or in combination with 20 µg/mL of fluconazole were evaluated for their antimicrobial activity on the fungus Fusarium solani, and the effects of these peptides on the permeability of membranes and the induction of oxidative stress were determined. Our results show that these peptides at a concentration of 400 µg/mL combined with 20 µg/mL of fluconazole were able to inhibit the growth of the tested fungi, promote changes in their growth pattern, permeabilize the membrane, and induce reactive oxygen species (ROS). Some of these results were also observed with the peptides alone or with fluconazole alone, suggesting that the peptides act synergistically, promoting the potentiation of antimicrobial action. In this study, it was shown that Cc-LTP2 and Cc-GRP in combination with fluconazole were able to inhibit the growth of the fungus F. solani, to promote permeabilization of its membrane, and to induce the production of ROS, suggesting a combinatorial activity between the peptides and fluconazole.